An exploratory study of a real-time choice procedure. Issue 1 (2nd January 2019) - Furrebøe, Elise F.; Holth, Per; Sandaker, Ingunn
ABSTRACT: In this exploratory study, we expand the research on choice using real outcomes in real-time settings. The object is to refine a method for examining the reinforcing contingencies in discounting, for which real rather than hypothetical settings are necessary. In the experiments, adult human participants chose between a smaller-sooner (SS) and a larger-later (LL) alternative, with an adjusting real delay to LL. We examined the use of points as the outcome and tested conditions concerning amount of outcome and delay. Second, we analyzed how differences in criteria for establishing an Indifference Point (IP) might determine the location of the IP. Finally, we performed a control experiment, introducing a decreasing delay and post-experimental questions, to determine whether the choices were a result of the adjusting delay or by molar considerations. This study gives support to the use of points as reinforcers and delay of seconds in discounting studies on human adults.